PREVALENCE OF INTESTINAL PARASITE AND RELATED FACTORS AMONG SCHOOL CHILDREN IN SUAN PHUENG SUBDISTRICT, RATCHABURI, THAILAND - Pyae Phyo Kyaw; Chirawat Paratthakonkun; Rapeeporn Yaicharoen; Reongwit Nilkote; Ngamphol Soonthornworasiri; Pattaneeya Prangthip; Pannamas Maneekan; Aung Phone Zaw; Sai Wai Yan Myint Thu; Dumrongkiet Arthan (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Intestinal parasitic infections are still regarded as the major public health problems in Thailand, especially in rural areas. The presence of intestinal parasites in school children is a well- accepted indicator of poor personal hygiene and low economic standards. This study aimed to determine the prevalence of intestinal parasitic infections and its associated risk factors among primary school children (Grade 4 to 6) in Suan Phueng sub-district, Ratchaburi, Thailand, where is located at Thai-Myanmar border areas. Methods: A cross-sectional study was conducted at three selected governmental primary schools. A total of 252 school children (130 boys, 51.6% and 122 girls, 48.4%) were recruited in this study. Intestinal parasites were detected from their stool samples by using formalin ethyl-acetate concentration technique. Socio-demographic status and personal hygiene were assessed by a validated structured questionnaire. Results: An overall prevalence of intestinal parasitic infection was 19%. Poly-parasitism was found in 4% of school children. The most common parasite was Entamoeba coli (6.4%) followed by Ascaris lumbricoides (4.5%), Endolimax nana cyst (4.0%), and Giadia lumbria (1.8%). Additionally, family income, drinking water sources from school and home, hand-washing habit after using toilet, anal cleansing after defecation, and parents’ education level were significantly associated with intestinal parasitic infections. Conclusions: High prevalence of intestinal parasitic infections was found in primary school children at Suan Phueng sub-district, Ratchaburi, Thailand. Therefore, health promotion, modern health education, water sanitation, and hygiene (WASH) programs are crucial for prevention of intestinal parasitic infections in primary schools, particularly in Thai-Myanmar border areas. Reducing the prevalence of parasitic infections in school children may be of immense benefits on child growth, development, and educational outcomes.